2008
DOI: 10.1097/nen.0b013e31815f38b7
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion Body Myositis Associated With Human T-Lymphotropic Virus-Type I Infection

Abstract: The objective of this study was to investigate the association of human T-lymphotropic virus-type I (HTLV-I) infection with sporadic inclusion body myositis in 11 patients from an endemic area in Japan. The clinical features were consistent with sporadic inclusion body myositis, and anti-HTLV-I antibodies were present in the sera of all patients. Their muscle biopsies showed the diagnostic features of inclusion body myositis, including endomysial T-cell infiltration, rimmed vacuoles, deposits of phosphorylated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 43 publications
0
38
0
2
Order By: Relevance
“…Myopathy can affect patients irrespective of the presence of other neurological manifestations. In one region of Japan, between 1986 and 2006, Matsuura et al 42 observed higher prevalence rates for the combination of inclusion body myositis and HTLV (11 out of 21 patients, 52.3%), than for polymyositis (27.5%), with a seropositivity rate of 11.6% in the general population. They identified a high proviral load and immune susceptibility as the principal factors in emergence of the pathological process.…”
Section: Polymyositis Inclusion Body Myositis and Fibromyalgiamentioning
confidence: 99%
“…Myopathy can affect patients irrespective of the presence of other neurological manifestations. In one region of Japan, between 1986 and 2006, Matsuura et al 42 observed higher prevalence rates for the combination of inclusion body myositis and HTLV (11 out of 21 patients, 52.3%), than for polymyositis (27.5%), with a seropositivity rate of 11.6% in the general population. They identified a high proviral load and immune susceptibility as the principal factors in emergence of the pathological process.…”
Section: Polymyositis Inclusion Body Myositis and Fibromyalgiamentioning
confidence: 99%
“…Entre las descritas hasta el momento figuran la leucemia o linfoma de células T, la paraparesia espástica tropical o miopatía asociada al HTLV, la uveítis, múltiples alteraciones dermatológicas, la miositis, la polimiositis, la polineuropatía, los trastornos psiquiátricos, las infecciones oportunistas, la infección por Strongyloides stercoralis y las condiciones reumatológicas autoinmunitarias (8)(9)(10). Se ha reportado la asociación entre el desarrollo de un tipo específico de enfermedad y la vía de transmisión del virus.…”
unclassified
“…HTLV-1 is the causative agent of adult T cell leukemia/lymphoma (ATL) (5) and HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) (6). Additionally, other diseases have also been associated with chronic HTLV-1 infection, including dermatologic conditions (7), uveitis (8), and myositis (9).…”
mentioning
confidence: 99%